The Fisher Effect in conventional and Islamic money markets in Malaysia - Zainal, Nurazilah (2014)
Current volatile environment in the global financial markets provides a challenging avenue to which the Malaysian financial system and economy would be in pressure by negative external forces. The global economy crisis in year 1998 and 2008 has brought many negative consequences to Malaysian economy as inflation is recorded high and increase in unemployment rate. In this condition, the movement between interest and inflation rates becomes tough to estimate. High inflation and high interest rates hamper economy growth by discouraging investment and reducing output of the country. This study examines the relationship between interest rates and expected inflation rates in Malaysia. Fisher (1930) postulates a theory that explained one-to-one relationship between interest rates and expected inflation rates. In Malaysia, previous empirical studies on the Fisher Effect have focused the relationship on conventional market, leaving Islamic market with no or very few studies. On the first objective, this study aims at assessing the validity of Fisher Effect between Conventional and Islamic Money Market in Malaysia. Time series data spanning from 2005 to 2012 is chosen as the study duration. Five variables are used in this study; they are Inflation Rate (INF), 3-months Treasury Bills Rate (MTB), Interbank Rate (IBR), 3-months Islamic Treasury Bills Rate (MITB) and Islamic Interbank Rate (IIR). In order to investigate the Fisher Effect, this paper employs the Autoregressive Distributed Lag (ARDL) approach that is capable of testing for the existence of a long-run cointegration between the variables irrespective of whether the time series that are being studied are I(0) or I(1). This analysis has also identified the relationship whether they are in a strong or weak form of Fisher Effect. The estimation results indicate the presence of Fisher Effect relationship on the basis of Islamic money market in Malaysia. However, the relationship appears in a weak form. For conventional market, no evidence of Fisher Effect has been found. For the second objective, this study examines the direction of relationship between interest rates and inflation rates in the short run. Although the existence of a long-run relationship among these variables has been identified, the direction whether the changes in interest rates is causing changes in inflation or changes in inflation is causing changes in interest rates is still inconclusive. For this purpose, this study employs a Granger causality test developed by Granger 1969). The findings revealed that the IBR, MITB and IIR have unidirectional relationship with inflation rate in the short run. However, no directional relationship has been found between MTB and Inflation rates. Overall the study provides supportive evidence on the importance of Fisher Effect theory and the results help monetary authorities to formulate better monetary policy in future (Ito, 2009). Other than that, the results also help the investors by giving direction on the behaviour of inflation rates so that they can preserve their value of money and invest in better investment vehicles.